Palliative care production for health professionals in the context of home care - Alexandre Ernesto Silva; Elysângela Dittz Duarte; Sérgio Joaquim Deodato Fernandes
ABSTRACT Objectives: to analyze palliative care production developed by health professionals to home care patients. Methods: this is an exploratory study, with a qualitative approach, using the transpersonal care theoretical framework. Thirteen interviews were conducted with health professionals and 18 observations were conducted on different cases. Content analysis was performed using MAXQDA©. Results: actions performed: maintenance and follow-up measures to people eligible for palliative care, in acts of dialogue and "listening" to caregivers and users, conducting guidelines for the care and self-care process, performing technical procedures, delivery of materials, referrals and medical prescriptions to users. Final Considerations: it is perceived the need for advances in the implementation of government policies in Brazil that insert palliative care into the Health Care Network through educational, managerial and care actions that ensure human dignity, thus allowing the development of these and other palliative care interventions.